REINTERPRETASI HADIS-HADIS INTOLERANSI AGAMA DALAM KUTUB AL-TIS’AH (KAJIAN TEMATIK) - Eka Tresna Setiawan (UIN Siber Syekh Nurjati Cirebon, 2017)
Islam is a religion that has the principle of compassion for all nature (rahmatan lil ‘a> lami> n) and tolerance. The problem is, among the traditions of the Prophet Muhammad, there are some who outwardly appear intolerant of non-Muslims. This study aims to explain the concept of tolerance among adherents of religions in Islam, explaining the existence of intolerant traditions of adherents of religions in the pole of al-Tis'ah, and explaining the reinterpretation of these traditions. This research is a type of library research with a qualitative approach and deductive analysis techniques. The theory taken is ikhtilaf al-hadith, namely jam'u, tarjih and naskh by using the priority of jam'u through universal, temporal and local contextualization. The results of this study are First, Islam is a religion that upholds tolerance among religious people, as reflected in the verses of the Qur'an and hadith of the Prophet. Second, there are several intolerant traditions in the al-tis'ah pole, namely the rejection of co-existence, rejection of appreciation and rejection of co-existence. Third, the result of the reinterpretation is that the traditions that appear intolerant are temporal traditions.